Jurnal otonomi daerah. - Indonesia. Direktorat Jenderal Otonomi Daerah (Jakarta : Direktorat Jenderal Otonomi Daerah, Departemen Dalam Negeri dan Otonomi Daerah, 2001)
On decentralization of local government in Indonesia.
Description based on: Th. 1, no. 3 (Des. 2001); title from cover.
Keywords: Local government -- Indonesia -- Periodicals; Decentralization in government -- Indonesia -- Periodicals